The fossil record of turtles in colombia; a review of the discoveries research and future challenges (2014)
This is a review article on the fossil record of turtles in Colombia that includes: the early Cretaceous turtles from Zapatocaand Villa de Leyva localities; the giant turtles from the Paleocene Cerrejón and Calenturitas Coal Mines; the early Miocene,earliest record of Chelus from Pubenza, Cundinamarca; the early to late Miocene large podocnemids, chelids and testudinidsfrom Castilletes, Alta Guajira and La Venta; and the small late Pleistocene kinosternids from Pubenza, Cundinamarca. I alsodiscuss here the current gaps in the fossil record of tropical South American turtles, as well as the ongoing research and futureprojects to be developed in order to understand better the evolutionary history of Colombian turtles.El registro fósil de las tortugas en Colombia; una revisión delosdescubrimientos investigaciones y futuros desafíosEn este artículo resumo el registro fósil de tortugas de Colombia, incluyendo las tortugas del Cretácico temprano de Zapatocay Villa de Leyva, las tortugas gigantes del Paleoceno en las minas de carbón de El Cerrejón y Calenturitas, el registro másantiguo de Chelus, proveniente del Mioceno temprano de Pubenza (Cundinamarca), los grandes podocnémidos, chélidos,y testudínidos del Mioceno temprano a tardío de Castilletes en la Alta Guajira y La Venta, y los pequeños kinostérnidos delPleistoceno tardío de Pubenza, Cundinamarca. En este artículo discuto también los actuales intervalos para los cuales nose conocen registro fósil de tortugas en la parte tropical de Suramérica, así como también las investigaciones que se estándesarrollando actualmente, c también los futuros proyectos a desarrollar con el fin de entender mejor la historia evolutiva delas tortugas en Colombia.